Comparative study of cortisol and leptin concentration in obese non-diabetics and obese with uncomplicated diabetes - Z. Tariqa, Siba; B El-amamyb, Adella; M. Zakokoa, Ahmed; A. Awada, alah; Y. Younisa, Mustafa; A. Benhasounac, Ahmed; A. El Gehanic, Khaled; A. Elshaaria, Farag (Libyan Journal of Science &Technology, 2024)
In addition to chronic hyperglycemia, the main characteristic feature of diabetes is the impairment of carbohydrate, fat, and protein metabolism that underline the main cause of short-term and late-developing disease complications. These lead to stern changes in body systems, notably, the increased activity of the hypothalamic-pituitary-adrenal (HPA) axis, and expectedly, the upstream/downstream changes in adipokines and cortisol. This study was undertaken to assess cortisol and leptin levels in relation to obesity and diabetes. Excluding patients with complications, twenty-eight obese type 2 diabetic patients (diabetes duration less than 10 years) were recruited for the study. All patients were receiving metformin doses of 500 mg or 850 mg. The controls included in the study were 16 non-diabetic apparently healthy obese volunteers. Fasting blood sugar (FBS), HbA1C, LDL, HDL, leptin, and cortisol were analyzed. In the diabetic group FBS, HbA1C, TAG, LDL, and total cholesterol were significantly higher compared to the obese non-diabetic group. Serum leptin and cortisol showed no significant differences between the diabetic and the obese control group at 95% confidence. However, in the diabetic group, significant correlations were seen between serum leptin and HDL, and strong correlations relating the bodyweight indicators (BMI; WC) with leptin and cholesterol. These results were expected to be the outcome of the cortisol changes in type2 diabetes, but no significant correlations were evident between serum cortisol and HbA1c. The outcome of the study was explained relating the similarity of the hormone's activity to the patients included in the study have had the disease for considerably short periods and were selected for lacking the complications usually seen in chronic long-duration diabetes.